Design analysis and performance evaluation of the WDM integration with CO-OFDM system for radio over fiber System - Adnan Hussein Ali; Hayder Jasim Alhamdane; Begared Salih Hassen (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The optical communication and wireless networks can be integrated to increase the capacity and mobility with decrease the costs in the access networks. Optical communication is considered a Fiber optic communication that can be used for wired and wireless communication. The problems of Fiber optic communication have a solution represented by Radio over fiber (RoF) which can control many base stations (BSs) that connect to a central station (CS) with an optical fiber. The Coherent optical OFDM (CO-OFDM) have concerned a great interest due to the high spectral efficiency and strength to the fiber dispersion, also it can be considered as a promising candidate when used in long haul optical fiber transmission systems. The integration of the wavelength division multiplexing system (WDM) with (CO-OFDM) system for increasing the system performance as well as achieving high data rates. The simulation of WDM-ROF and  (WDM-CO-OFDM) with an optisystem simulator to analyze the RF spectrum, spectrum signal visualizers, and constellation diagrams. The proposed of integration of WDM and RoF-OFDM system is to achieve 100 km fiber length using 4QAM sequence bit, and the received power with electrical and optical amplifications by using 10 Gbps data signal.